2006
DOI: 10.1002/j.1556-6678.2006.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment, Self-Worth, and Depressive Symptoms Among Emerging Adults

Abstract: The characteristics of parental attachment were assessed for a sample of 81 emerging adults (ages 22-28 years) and their mothers. Emerging adults' reports of self-worth were found to mediate the relationship between their reports of parental attachment and depressive symptoms. The emerging adults' unique perspectives of the attachment relationship were more predictive of their self-reported self-worth and depressive symptoms than were the mothers' perspectives of the relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 51 publications
5
92
0
Order By: Relevance
“…The idea that attachment is an essential ingredient for healthy human development has been fortified by the increasing attention in applying attachment theory to areas of the life span beyond infancy (Kenny & Sirin, 2006). Studies have found that people continue to develop in view of attachmentrelated experiences throughout childhood, adolescence, and early adulthood (Hunnum & Dvorak, 2004;Lopez & Brennan, 2000).…”
Section: Parental and Peer Attachment And Depressive Symptomsmentioning
confidence: 99%
“…The idea that attachment is an essential ingredient for healthy human development has been fortified by the increasing attention in applying attachment theory to areas of the life span beyond infancy (Kenny & Sirin, 2006). Studies have found that people continue to develop in view of attachmentrelated experiences throughout childhood, adolescence, and early adulthood (Hunnum & Dvorak, 2004;Lopez & Brennan, 2000).…”
Section: Parental and Peer Attachment And Depressive Symptomsmentioning
confidence: 99%
“…Those with higher levels of extrinsic motivation, combined with decreased parental support, were more likely to have unclear ideas about their career futures and lack commitment toward their jobs. For these emerging adults, their rates of depression also significantly increased over the seven years, a common symptom in emerging adults overall (Kenny & Sirin, 2006), which further confirms the importance of personal self efficacy in exploring meaning in one's life.…”
Section: This Process Of Authenticity Mirrors Key Components Of Savicsupporting
confidence: 54%
“…Duffy and Sedlacek (2007) found that college students' search for life meaning negatively correlated with psychological factors, including purpose in life, self-esteem, and life satisfaction, as well as career outcomes, such as career decidedness and self-clarity. The demographic delay in marriage and parenthood also increases the pressure to find the right career after graduating (Arnett et al, 2014;Kenny & Sirin, 2006).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations